"Submitting Love?" A Sensory Sociology of Southbourne. (March 2016) - Dean, Jon
This article seeks to remember the Southbourne building of Sheffield Hallam University, United Kingdom, which housed students, academics, and administrative staff until August 2014. Data were collected from an ethnographic observation study of students handing in completed coursework. Findings are presented in the form of an audio "soundscape" and a literary narrative. It is argued that these hypermodal tools should form a growing part of qualitative inquiry as sensory social research. The historic application and practical impediments of such sensorial and aural techniques are discussed, alongside the challenge they provide to the received practices concerning how journal articles can be experienced.